Sensitivity of Volumetric Magnetic Resonance Imaging and Magnetic Resonance Spectroscopy to Progression of Spinocerebellar Ataxia Type 1. Issue 7 (10th July 2019) - Deelchand, Dinesh K.; Joers, James M.; Ravishankar, Adarsh; Lyu, Tianmeng; Emir, Uzay E.; Hutter, Diane; Gomez, Christopher M.; Bushara, Khalaf O.; Lenglet, Christophe; Eberly, Lynn E.; Öz, Gülin
ABSTRACT: Background: Spinocerebellar ataxia type 1 (SCA1) causes progressive degeneration of the cerebellum and brainstem. Volumetric magnetic resonance imaging (MRI) was shown to be more sensitive to disease progression than the most sensitive clinical measure, the Scale for the Assessment and Rating of Ataxia (SARA), in longitudinal studies, and magnetic resonance spectroscopy (MRS) was shown to detect neurochemical abnormalities with high sensitivity cross‐sectionally in SCA1. Objectives: The objectives of this study were to compare the sensitivities to change of volumetric MRI, MRS, and SARA in a 3‐year longitudinal study in SCA1. Methods: A total of 16 early‐to‐moderate stage patients with SCA1 (SARA 0‐14) and 21 matched healthy participants were scanned up to 3 times with 1.5‐year intervals. Ataxia severity was assessed with SARA. T1 ‐weighted images and magnetic resonance spectra from the cerebellar vermis, cerebellar white matter, and pons were acquired at 3T. Results: The pontine total N ‐acetylaspartate‐to‐ myo ‐inositol ratio was the most sensitive MRS measure to change (−3.9 ± 4.6%/yr in SCA1 vs. −0.3 ± 3.5%/yr in controls; P < 0.02), and the pontine volume was the most sensitive MRI measure to change (−2.6 ± 1.2%/yr in SCA1 vs. −0.1 ± 1.2 in controls; P < 0.02). Effect size (mean percent change/standard deviation of percent change) of pontine volume was highest (−2.13) followed by pontine N ‐acetylaspartate‐to‐ myo ‐inositol ratio (−0.84) and SARA (+0.60). The pontine N ‐acetylaspartate‐to‐ myo ‐inositol ratio was abnormal for 1 premanifest patient at all visits and predicted study withdrawal as a result of disease progression in 3 patients. Conclusion: Both MRI and MRS were more sensitive to disease progression than SARA in SCA1. Pontine volume was most sensitive to change, whereas MRS may have more sensitivity at the premanifest stage and predictive value for disease progression.